Offshore Urbanism: Using design to understand, represent and employ human-sea relations in the spatial reorganisation of the Barents Sea - Kreulen, Marijne (author) (2021)
This thesis builds on the proposition that the ocean is both an urban and social space. Therefore, marine planning needs to consider socio-cultural risks and opportunities to be deemed sustainable. This reconceptualisation is especially relevant for the Barents Sea, where retreating sea ice leaves the ocean more accessible to marine traffic and resource extraction every year. However, the current practice of marine spatial planning (MSP) responds predominantly to geopolitical and economic demands for resources like gas and oil - only the monetary value of the ocean is considered. It fails to provide an understanding of the ocean as a space of cultural values, memory, and meaning. As a result, the socio-cultural impacts of offshore development remain alarmingly unmapped and unknown. As an interplay between research and design, urbanism can understand human-sea relations and employ this understanding in spatial interventions, where MSP cannot. Following this hypothesis, I aim to approach the Barents Sea as an urban and local project. What does it mean to be at sea, to be changed by the sea, and to change it in return? How is the local economy of life dependent on conditions of marine space? And how can urban designers use this knowledge to affect change. In the first place, this is a theoretical work. I hypothesize what offshore urbanism should entail, propose entrances of design, and compose design principles in the Barents Sea. The theory is tested in a case study: the coastal community of Hammerfest. The current network composition of the Hammerfest maritory shows a system that is overdependent on petroleum activity. The project proposes two pathways of change towards a future where Hammerfest depends on a variety of alternative marine industries. As such, the community becomes more resilient to changes in offshore petroleum. Particularly after 2035, when the current production fields are depleted and extraction moves seaward, away from Hammerfest. Network analysis forms a key point of entrance for the ...